INTERACTIVE CD TO IMPROVE VOCABULARY MASTERY FOR THE FIFTH GRADE STUDENT OF MI AT-TARAQQIE MALANG - Lamya Hayatina (MPP: Lembaga Penelitian Dan Studi Kebijakan, 2021)
Vocabulary is one of important factors in language skills. The learner of language faces difficulty if they are lack of vocabulary. Therefore, the teacher has to creates or using such of good, interesting, and new technique in teaching vocabulary that is able to raise the motivation of students to learn and achieve it. One of the techniques in teaching vocabulary is by using interactive CD as media. The researcher chooses interactive CD media, because picture, song, games, story are interesting for everyone, especially for children, and to change bored situation become a happiness, and enjoyable. Interactive CD is considered important to assist the instruction and facilitate the students’ vocabulary mastery. By using media, the materials in vocabulary can be more understandable, learning activities become more interesting, and the teachers can use various activities in their instruction. Instructional media are also very beneficial in English Language Teaching. This researcher was done at MI At-Taraqqie Malang. The research method used of this study is Classroom Action Research (CAR). It is focusing on particular group of the students at the fifth grade of MI At-Taraqqie Malang. The research instruments that used by the researcher on this study are test, observation, questionner, and interview. There are two cycles of this research. The result of cycle I was not successful because the students’ average score was 67.70. It did not achieve the criteria of success. Therefore, the researcher continued to the next cycle, by revising the plan in cycle I. In cycle II, the students’ average score was 75.67, meaning that the result had fulfilled the criteria of success. And the students’ response was better than previous cycle. So, the researcher stopped this research. Finally, the result of the study shows that interactive CD can develop their vocabulary. They are not bored, but students look braver and more confident. They also became full of concentration in the classroom during the teaching-learning process. Based on the researcher finding, it can be concluded that teaching vocabulary using interactive CD can improve the students’ vocabulary mastery. The students’ score is getting better in each cycle. It indicates that the teaching-learning process is successful